Baseline CD4+ T-cell Count and Cardiovascular Risk Factors Predict the Evolution of Cognitive Performance During 2-Year follow-up in HIV-Infected Patients. Issue 4 (May 2015) - Ciccarelli, Nicoletta; Grima, Pierfrancesco; Fabbiani, Massimiliano; Baldonero, Eleonora; Borghetti, Alberto; Milanini, Benedetta; Limiti, Silio; Colafigli, Manuela; Tamburrini, Enrica; Cauda, Roberto; De Luca, Andrea; Giambenedetto, Simona Di
Background: The aim of our study was to better understand the dynamics between cardiovascular risk factors and immunological parameters in the evolution of cognitive performance in HIV+ patients. Methods: We conducted a prospective longitudinal study, consecutively enrolling asymptomatic HIV+ subjects during routine outpatient visits at two clinical centres. At baseline and after 2 years, all patients underwent a comprehensive neuropsychological battery. Common carotid intima-media thickness (cIMT) was also measured. Results: A total of 150 patients completed the study (77% males, median age 46 years, 20% with past AIDS-defining events, 95% on cART, 88% with HIV-RNA<50 copies/ml). After a 2-year follow-up, there was no difference in the proportion of patients with cognitive impairment (32% versus 33% at baseline; P =1.00). However, a significantly worse memory performance was observed (z score mean change -0.51, sd 1.05; P =0.001). At multivariate analysis, baseline dyslipidaemia (OR 2.7, 95% CI 1.1, 7.1; P =0.037) showed a significant association with a higher risk of memory impairment at 2-year follow-up, while higher baseline CD4 + T-cell count (OR 0.80 per 100 cells/ ml higher; 95% CI 0.66, 0.97; P =0.026) was found to be a protective factor, adjusting for the presence of a memory impairment at baseline. When the analysis was restricted to patients who did not change antiretroviral therapy during the study period ( n =109), baseline cIMT (OR 14.6 per 0.1 mm higher; 95% CI 1.1, 189.9; P =0.041) also emerged as an independent risk factor for memory impairment at 2-year follow-up. Conclusions: Immunological parameters and cardiovascular risk factors are independently associated with the evolution of cognitive status in HIV+ patients.